Nighttime eating during pregnancy and infant adiposity at 6 months of life - Rodríguez-Cano, Ameyalli M.; Medel-Canchola, Berenice; González-Ludlow, Isabel; Rodríguez-Hernández, Carolina; Reyes-Muñoz, Enrique; Schiffman-Selechnik, Esther; Estrada-Gutierrez, Guadalupe; Perichart-Perera, Otilia (Frontiers in Nutrition, 2024)
Introduction Chrononutrition studies the relation between diet, circadian rhythms and metabolism, which may alter the metabolic intrauterine environment, influencing infant fat-mass (FM) development and possibly increasing obesity risk. Aim To evaluate the association of chrononutrition in pregnancy and infant FM at 6 months. Methods Healthy pregnant women and term-babies (n = 100pairs) from the OBESO cohort (2017–2023) were studied. Maternal registries included pregestational body-mass-index (BMI), gestational complications/medications, weight gain. Diet (three 24 h-recalls, 1 each trimester) and sleep-schedule (first and third trimesters) were evaluated computing fasting (hours from last–first meal), breakfast and dinner latencies (minutes between wake up-breakfast and dinner-sleep, respectively), number of main meals/day, meal skipping (≥1 main meal/d on three recalls) and nighttime eating (from 9:00 pm–5:59 am on three recalls). Neonatal weight, length, BMI/age were assessed. At 6 months, infant FM (kg, %; air-displacement plethysmography) was measured, and FM index (FMI—kgFM/length2) computed. Exclusive breastfeeding (EBF) was recorded. Multiple linear regression models evaluated the association between chrononutrition and 6 month infant FM. Results Mean fasting was 11.7 ± 1.3 h; breakfast, dinner latency were 87.3 ± 75.2, 99.6 ± 65.6 min, respectively. Average meals/day were 3.0 ± 0.5. Meal skipping was reported in 3% (n = 3) of women and nighttime eating in 35% (n = 35). Most neonates had normal BMI/age (88%, n = 88). Compared to those who did not, mothers engaged in nighttime-eating had infants with higher %FM (p = 0.019). Regression models (R2 ≥ 0.308, p ≤ 0.001) showed that nighttime eating was positively associated with %FM (B: 2.7, 95%CI: 0.32–5.16). When analyzing women without complications/medications (n = 80), nighttime eating was associated with higher FM [%FM, B: 3.24 (95%CI: 0.59–5.88); kgFM, B: 0.20 (95%CI: 0.003–0.40); FMI, B: 0.54 (95%CI: 0.03–1.05)]. Infant sex and weight (6 months) were significant, while maternal obesity, pregnancy complications/medications, parity, energy intake, birth-BMI/age, and EBF were not. Conclusion Maternal nighttime eating is associated with higher adiposity in 6 month infants.